EDUCATION, AWARENESS AND CONSERVATION OF ROMANIA'S BIODIVERSITY - Cristiana Silvia BUZATU; Iulian Virgil GHIULEANU; Valentina Constanța TUDOR; Răzvan PANAIT (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Romania's biodiversity is a natural treasure, offering a vast array of species and ecosystems, but faces increasing threats from human activities and climate change. Education, awareness and conservation of biodiversity are key to protecting this priceless biological diversity. In this article, through statistical methods of analysis, we aim to explore the role of education and awareness in the conservation of Romania's biodiversity, highlighting initiatives and efforts to promote public understanding and commitment to protecting the environment and unique species. This analysis allowed us to identify relevant patterns, trends and conclusions related to biodiversity education, awareness and conservation in Romania. Protecting Romania's biodiversity is therefore not only a necessity for the environment, but also for society, the economy and human well-being. Biodiversity conservation is essential for our well-being and the health of the planet, and it is our responsibility to act on it. We will explore the importance of education in schools and universities, the role of NGOs and government actions, and their impact on biodiversity conservation in the country.